A reversible hypocalcemic dilated cardiomyopathy caused by primary hypoparathyroidism - Cheng, Zhenli; Yadav, Shiv Kumar; Liu, Xiaoyan; Yi, Qijian (Asian Journal of Medical Sciences, 2019)
Dilated cardiomyopathy (DCM) is characterized by dilation and impaired contraction of one or both ventricles. Affected patients have impaired systolic function and may or may not develop overt heart failure (HF). Prognosis is generally poor without heart transplantation. We experienced a case of a 10-year-old child with dilated cardiomyopathy (DCM) accompanied by undiagnosed primary hypoparathyroidism. In our case,aggressive management of hypoparathyroidism significantly improved the manifestations of DCM. The case presentation highlights the importance of considering hypoparathyroidism as a cause of reversible myocardial dysfunction.